2005
DOI: 10.1227/01.neu.0000180810.16964.3e
|View full text |Cite
|
Sign up to set email alerts
|

Permanent Neurological Deficit Related to Magnetic Resonance Imaging in a Patient with Implanted Deep Brain Stimulation Electrodes for Parkinson's Disease: Case Report

Abstract: To prevent catastrophic incidents, the manufacturer's guidelines should be followed carefully because they are known to result in the safe performance of MRI examinations of patients with neurostimulation systems used for DBS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
219
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 266 publications
(221 citation statements)
references
References 4 publications
0
219
0
2
Order By: Relevance
“…78,79 The principal manufacturer of DBS systems states that MR imaging is contraindicated in patients with DBS unless specific precautions are taken. If these precautions are taken, MR imaging can and has been performed in many cases safely, but the patient and physician must be aware of the potential MR imaging hazards.…”
mentioning
confidence: 99%
“…78,79 The principal manufacturer of DBS systems states that MR imaging is contraindicated in patients with DBS unless specific precautions are taken. If these precautions are taken, MR imaging can and has been performed in many cases safely, but the patient and physician must be aware of the potential MR imaging hazards.…”
mentioning
confidence: 99%
“…The safety of the MRI scan is another issue with those who were keeping DBS electrodes in their brains 13,22,36) . In 2000, Yamamoto et al first reported a case of thalamic lesioning in a patient treated with a thalamic DBS after emergent cardioversion for the treatment of severe arrhythmia of the patient 36) .…”
Section: Discussionmentioning
confidence: 99%
“…In 2000, Yamamoto et al first reported a case of thalamic lesioning in a patient treated with a thalamic DBS after emergent cardioversion for the treatment of severe arrhythmia of the patient 36) . In 2005, Henderson et al described a case of serious, permanent neurological injury secondary to a radiofrequency lesion produced by the heating of a DBS electrode associated with the MR image scanning of the lumbar spine in a patient with PD 13) . With those anec-dotal occurrences of severe adverse effects related with DBS in the brains, the FDA issued a warning about the possible significant side effects when brain MRIs were performed on patients with a DBS in their brain.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of severe injury with the lead inserted into the brain when a 1.5-T MRI scan is performed has been already reported but has to be counterbalanced with the large number of patients in whom MRI scans, using head coils, have been performed also without any problems [4,6,16,25]. While some isolated MR complications occurred in implanted patients, with the need to modify safety rules [7,9,21], many teams reported accuracy, innocuousness, and advantages of its use.…”
Section: Feasibility and Technical Requirementmentioning
confidence: 99%